Exploring blockchain for KYC: deepening client understanding - Anuar, Muhammad Akmal; Khedher, Akram M Z M; Abubakar Ibrahim, Adamu (IEEE, 2023)
Examining one's client status in depth, also known by its acronym "Know Your Customer" (KYC), raises a significant problem that needs to be addressed thoroughly. As a result of this, the current paper examines the dynamics of client status and utilized "Blockchain Technology" to developed KYC. Since earlier research was lacking in its capacity to establish a KYC system, which is utilized in the financial sector, principally by banks, to collect information mandated by law regarding their customers in order to provide access to financial services, it is important to note this deficiency. The existing system makes use of databases that are hosted on servers operated by private corporations or by organizations that have their own infrastructures. Traditional KYC systems come with several potential drawbacks, including a single point of failure (SPOF), tedious and timeconsuming processes for customers, and high costs to construct one's own KYC identification and verification system. The aim of this project's proof-of-concept is to mitigate the effects of the identified issues through the utilization of blockchain technology. The system's ability to facilitate the data gathering and verification process was enhanced by the provision of previously registered KYC data by individual users through a single click, as well as the cross-checking of KYC data by bank users to verify their users' information.